Bat algorithm applied to continuous constrained optimization problems - Karakonstantis, Ioannis; Vlachos, Aristidis (Journal of information & optimization sciences, 2021)
Many optimization techniques have been proposed for solving economic load and or emission dispatch problems in power generation plants. Among them, bio-inspired techniques have become popular due to their performance and simplicity. Bat Algorithm (BA) is one of the newer additions in the field although it has been applied in a series of evaluation tests. The method is trying to replicate the echolocation behavior of bats with artificial ones. In this paper, we apply BA to the well-known problem of economic load dispatch, in different power demand scenarios. Its performance in terms of solution fitness is compared with other optimizations techniques proposed in the literature for the same scenarios.